THE PHENOMENON OF LANGUAGE IN ONTOLOGICAL, GNOSEOLOGICAL AND AXIOLOGICAL ASPECTS - Blyzniuk, Lesya; Tolstov, Ivan; Chernyshov, Victor (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2025)
The article presents a comprehensive philosophical analysis of language as a multidimensional phenomenon, integrating ontological, gnoseological, and axiological aspects closely connected to human existence, social reality, and cultural identity. Language is viewed not merely as a tool of communication but as a fundamental element shaping cognition, thought, perception, and social interaction. The study traces the evolution of philosophical reflection on language: from Plato and Aristotle’s inquiries into names, meaning, and the connection between language and thought, through medieval disputes between realism and nominalism concerning universals, to the twentieth century ‘linguistic turn’, which positioned language at the centre of philosophical investigation. Particular attention is given to contemporary interdisciplinary approaches, including cognitive linguistics and the analysis of relations between human language and artificial intelligence, highlighting the uniqueness of human linguistic activity and the ontological significance of grammatical categories such as person, tense, and relational structures. Ukrainian scholars’ contributions are examined, treating language as a bridge between ontology and gnoseology, emphasising its axiological dimension manifested in cultural value transmission, socialisation, and identity formation. Ontological analysis employs theories of meaning; gnoseological analysis examines the language/speech dichotomy and linguistic relativity; axiological analysis demonstrates language’s role in preserving and transmitting cultural, moral, and social norms. Language is concluded to constitute a universal semiotic space uniting being, knowledge, and values, whose integrated study enables deeper understanding of human cognition, communication, culture, and sociality, and opens avenues for further interdisciplinary inquiry.